Do encontro da literatura com a medicina - Margarida Reffóios (Carnets)
Having as a starting point examples taken from the French Literature we aim at analysing, at the light of Medicine, the diseases associated to the medieval woman.We will, thus, embark on a journey through the history of Medicine, showing how this Science of Knowledge is harmoniously combined in the literary text.To conclude, it is our desire to prove the specificity and the effectiveness of aspects of a common culture which, in the current context, benefits the multidisciplinary among different arts, already common in the 12th Century.